Total aflatoxins in complementary foods produced at community levels using locally available ingredients in Ethiopia. Issue 2 (3rd April 2018) - Ayelign, Abebe; Woldegiorgis, Ashagrie Zewdu; Adish, Abdulaziz; De Saeger, Sarah
ABSTRACT: This study was conducted to determine the occurrence and levels of total aflatoxins in complementary foods (CFs) and their ingredients. A total of 126 samples collected from 20 Districts from Amhara, Tigray, Oromia, and Southern Nations Nationalities and Peoples (SNNP) regions were analysed for levels of total aflatoxins using enzyme linked immunosorbent assay (ELISA). Aflatoxins were detected in 62 out of 66 pre-milling samples with mean range of 0.3–9.9 µg/kg. Aflatoxins were also detected in 19 out of 20 post-production CFs and in all of the one-month stored CFs at households and grain banks, with a mean range of 0.5–8.0, 3.6–11.3, and 0.2–12.4 µg/kg, respectively. Overall, 3 out of 126 samples exceeded the maximum limit (10 µg/kg). Although most aflatoxin levels were below the maximum limit and thus considered to be safe for consumption, more effort should be implemented to reduce contamination, as these CFs are intended for consumption by young children.